COMPARATIVE PERFORMANCE OF PUBLIC AND PRIVATE SECTOR BANKS IN DISBURSING MUDRA LOANS IN NAGPUR DISTRICT - Akhre, Ashish Vitthalrao; Gongale, Rekchand Ganpat (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The objective of this research paper is to critically assess and compare the performance of public and private sector banks in disbursing MUDRA (Micro Units Development and Refinance Agency) loans in Nagpur district. MUDRA loans are designed to promote micro-enterprises and provide financial assistance to the under-served and unbanked sections of the society. The study examines various aspects of loan disbursement, including the total volume of loans disbursed by both public and private banks, the demographic profile of the borrowers, the different categories of loans offered and the repayment performance of these loans. Through this in-depth analysis, we have attempted to find out how effectively these banks are contributing to the growth and sustainability of micro-enterprises in Nagpur. By comparing the strengths and challenges faced by both sectors, the research aims to provide a comprehensive understanding of their role in enhancing financial inclusion. The findings will provide important insights on how banks can improve their support for small entrepreneurs, thereby boosting economic growth at the grassroots level.